External relations and local agency in the Horn of Africa - Ylönen, A. (Current History, 2023)
Strategic and security analysis of the Horn of Africa systematically portrays the roots of instability as external. However, the region’s stability or instability is largely determined by local actors and conditions. Local agency and context largely set the conditions for the involvement of external actors. This article discusses how state and nonstate actors have conducted their engagement with outside powers, especially the Gulf states, at a time of increasing rivalry for influence in the Horn of Africa, with examples ranging from Ethiopia to Somalia, and from Djibouti to Somaliland.